Internal and External Factors Influencing Individual's Participation in Zakat: Preliminary Results - Muhamad Muda; Ainulashikin Marzuki; Amir Shaharuddin (Universiti Sains Islam Malaysia, 2024)
Zakat is one of the sources of funds available within the Islamic economic and financia1 systems. Although it is obligatory, the amount collected is relatively very small compared to income tax collections. One of the reasons could be la& of motivation among Muslims. n i e aim of this study is to investigate the factors affecting individual decisions in zakat contribution. In this exploratory study, factor analysis has been used. The main dimensions were characterised by interna1 and external factors. Using the principal component method, principal factor analyses identified five factors. These were the "altruism", "level of faith", "self-satisfaction", and "utilitarian" that represent internal factors, and "organization" dimensions that reflect externa1 factor. Further analysis indicates that the "altruism" has the highest score followed by faith (iman), self satisfaction, organization, and utilitarian factors. Based on the sample surveyed, the initial findings indicate that participation in zakat is not only motivated by internal factors but also the external factors.